PENGAWASAN TERHADAP PENDISTRIBUSIAN BAHAN BAKAR MINYAK BERSUBSIDI OLEH DINAS PERIKANAN KABUPATEN MERAUKE BERDASARKAN UNDANG-UNDANG NOMOR 7 TAHUN 2016 TENTANG PERLINDUNGAN DAN PEMBERDAYAAN NELAYAN, PEMBUDI DAYA IKAN DAN PETAMBAK GARAM - Rumbewas, Ricky Nelson; Bemo, Abdul Faris (Animha Law Journal, 2024)
This study aims to determine how the supervision of the Distribution of Subsidized Fuel Oil by the Merauke Regency Fisheries Service to Small Fishermen in Merauke Regency. This research is an Empirical Juridical Research. This research was conducted in the Merauke City Area, namely at the Arafura Buti Street Fuel Oil Station, and the Merauke Regency Fisheries Service. The results of the research in this thesis indicate that the regulation of the distribution of subsidized fuel oil by the Fisheries Service in distributing BBM uses a targeted distribution strategy by providing recommendations for purchasing subsidized fuel oil to fishermen. At the supervision stage, the government uses two instruments, namely control through recommendations given to small fishermen and supervision by assigning employees from the service to carry out supervision.